Kinetic And Correlation Studies Between Varying Corrosion Parameters And Corrosion Rate Of N-80 Oil Well Tubular Steel In 15% Hydrochloric Acid Pickling Solution Using Ficus Abutilifolia Plant Extract (International Journal of Engineering and Computer Science, 2013)
The varying effects of temperature, time and inhibitor concentrations on the corrosion rate of N-80 oil well tubular steel in 15% hydrochloric acid with and without leave extract of Ficus Abutilifolia have been investigated. The time, temperature and concentration of inhibitor were varied in the range 1-2.5 hrs at 0.5 hr interval, 45oC-90 oC at 15 oC interval and 0.1 – 0.9 v/v% at 0.1v/v% interval respectively. Standard deviation, effect of variables at 95% confidence interval, factorial design, and Arrhenius kinetics approach were used to correlate the corrosion parameters and corrosion rate. The obtained results indicate that temperature increase enhances corrosion rate while increase in inhibitor concentration and time decreases corrosion rate. It was found also that temperature and inhibitor concentration are the most important control parameters for corrosion process. The kinetic and statistical approaches were in good agreement.